IMPLEMENTASI GERAKAN LITERASI SEBAGAI UPAYA DALAM MENINGKATKAN KEMAMPUAN MEMBACA, MENULIS DAN BERPIKIR KRITIS SISWA KELAS 2 DAN 5 MADRASAH IBTIDAIYAH AL FATAH JATISARI TAJINAN - Rofiqoh Firdausi, Moh.Khoridatul Huda (PRODI PAI FIK UNIRA MALANG, 2024)
Schools play an important role in developing students' skills through various effective learning systems to achieve their learning goals. one way is to foster a love of reading, support to foster a love of reading. Literacy in schools has been implemented in many various madrasas, through program activities carried out. The aim of this study is to: (1) Explain the application of the literacy movement to improve the literacy and critical thinking skills of MI Al Fatah Jatisari Tajinan Malang students. (2) Explain the impact of implementing the literacy movement on increasing the literacy and critical thinking skills of MI Al Fatah Jatisari Tajinan Malang students. (3) Describe the success factors and obstacles in carrying out literacy training to improve students' literacy and critical thinking skills at MI Al Fatah Jatisari Tajinan Malang. The data collection techniques used were observation, interviews and documentation. Then the data is analyzed by reducing the data, displaying the data and drawing conclusions. And the results of the research are carrying out a literacy movement at MI Alfatah Kautsar to improve reading, writing and critical thinking skills.